2009
DOI: 10.1177/112070000901900309
|View full text |Cite
|
Sign up to set email alerts
|

Early Results of a New Highly Porous Modular Acetabular Cup in Revision Arthroplasty

Abstract: The 'Tritanium'acetabular cup has been successful in achieving rapid osseointegration with few complications. The management of pelvic discontinuity continues to be a challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…When compared to previous reports this showed that there was a statistically significant difference in aseptic loosening between hips with major and minor bone loss (2.9 % and 0.4 %; P =0.005). At this time to the best of our patients who had AAOS type 1 to type 4 acetabular defects using titanium based highly porous metals [40]. At a mean follow-up of 18.2 months (13-24 months), the authors found that 98 % of the cups (n = 42) had osseointegration at 12 weeks follow-up.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…When compared to previous reports this showed that there was a statistically significant difference in aseptic loosening between hips with major and minor bone loss (2.9 % and 0.4 %; P =0.005). At this time to the best of our patients who had AAOS type 1 to type 4 acetabular defects using titanium based highly porous metals [40]. At a mean follow-up of 18.2 months (13-24 months), the authors found that 98 % of the cups (n = 42) had osseointegration at 12 weeks follow-up.…”
Section: Discussionmentioning
confidence: 79%
“…Metal augments were used concurrently with the highly-porous acetabular components in 26 % of the 1,152 reported revisions, and bone grafting was used in 60 % of the patients (n =789). There was only one study reporting the use of titanium-based highlyporous metals for acetabular reconstruction while the remaining studies were on tantalum [40]. None of the studies except one analysed in this review reported on complications related to metal debris at final follow-up.…”
Section: Study Characteristicsmentioning
confidence: 97%
“…Canine and human studies using Tritanium (60-70% porous Ti scaffold manufactured using LTAVD) with a similar nano/microtexture as Trabecular Metal TM demonstrated optimistic but not as successful results compared to Ta in vivo. 36,37 Therefore, the chemistry and topography of Ta has a profound effect on osteoblast behavior, however, the exact mechanism for the dramatic increase in cell proliferation on Ta needs further exploration since it may have therapeutic potential in cases of compromised bone formation, such as in aging.…”
Section: Tantalum Stimulates Proliferationmentioning
confidence: 99%
“…However, after revision THA, patients are left nonweightbearing for no longer than 12 weeks to allow for implant stabilization by bone ingrowth; therefore, bone graft substitutes taking longer than 12 weeks to be effective are not practical. Also, no prior DBM studies utilized the new higher porosity implants now common in revision THA [5,17,24,27,29], even though implant surface topography influences bone ingrowth [6,15,16,23,38].…”
Section: Introductionmentioning
confidence: 99%